Characterization Study Of Malaysian ION-Adsorption Clay NR-REE (Non-Radioactive Rare Earth Element) - Nurul Izzah, Abd Bashid (Universiti Sains Malaysia, 2022)
The REE industry has recently paid a lot of attention to ion-adsorption clays (IAC), as many possible sources of REEs that are worth researching are those connected to ion adsorption clays. This study focuses on the characterization method of ion-adsorption clay from Kedah, Malaysia, comprises of two samples, one from overburden area, and another one from tailing area. The samples from overburden area were assigned as KDO (Kedah Overburden), meanwhile, samples from tailing area were assigned as KDT (Kedah Tailing Area). After separating the clay minerals from the samples to create oriented clay samples, the remaining clay minerals are examined using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), Particle Size Analysis (Malvern) and Fourier Transform Infrared Spectroscopy (FTIR). Halloysite, kaolinite, and quartz are clay minerals found in the area. For XRF Analysis, the major traced elements that were found in both of the samples are Silicon (Si), Potassium (K), Aluminium (Al) and Iron (Fe). Both samples have an abundance of quartz in both samples. Loss of Ignition is done prior to XRF analysis, and the results showed that KDT has LOI of 9%, while KDO with 5.8%. This shows that KDT has higher organic substances then KDO. For ICP-MS, the results indicate that all 17 elements of REEs are present in both samples, For Light Rare Earth Elements (LREE) and Heavy Rare Earh Element (HREE) content for KDO is higher than KDT, meanwhile the ratio for LREE to HREE for KDO is 1.17, lower than KDT with 4.41 ratio.